2012
DOI: 10.1525/bio.2012.62.5.12
|View full text |Cite
|
Sign up to set email alerts
|

Finding Common Ground for Biodiversity and Ecosystem Services

Abstract: polasky, heatheR tallis, haRold a. Mooney, and anne laRigaudeRieRecently, some members of the conservation community have used ecosystem services as a strategy to conserve biodiversity. Others in the community have criticized this strategy as a distraction from the mission of biodiversity conservation. The debate continues, and it remains unclear whether the concerns expressed are significant enough to merit the opposition. Through an exploration of the science of biodiversity and ecosystem services, we find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(36 citation statements)
references
References 18 publications
0
33
0
3
Order By: Relevance
“…Recently, some members of the conservation community have preferred the maintenance of ecosystem services as a strategy to conserve biodiversity, while others have criticized this strategy as a distraction from the aim of biodiversity conservation (Reyers et al, 2012). Recent research did not show the accordant options regarding the existence of strong relationships between the positive effects of biodiversity and ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some members of the conservation community have preferred the maintenance of ecosystem services as a strategy to conserve biodiversity, while others have criticized this strategy as a distraction from the aim of biodiversity conservation (Reyers et al, 2012). Recent research did not show the accordant options regarding the existence of strong relationships between the positive effects of biodiversity and ecosystem services.…”
Section: Introductionmentioning
confidence: 99%
“…Most examples of where biodiversity and ecosystem service trade-offs arise concern provisioning services [8,9]. The Millennium Ecosystem Assessment [8] defined provisioning services as 'products obtained from ecosystems' and found that trade-offs between these services and biodiversity have been the largest driver of biodiversity loss over the last 50 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent statement by Reyers et al 3 that "the concept of biodiversity emerges from an intrinsic context" echoes earlier studies, including the previous assertion by Reyers and colleagues 4 that "biodiversity and ecosystem services are associated with different values (intrinsic vs. utilitarian)" (see also 5 ). However, Reyers et al 3 do suggest "common ground" based on biodiversity’s additional links to ethical, spiritual, and religious values.…”
Section: Common Groundmentioning
confidence: 71%
“…However, Reyers et al 3 do suggest "common ground" based on biodiversity’s additional links to ethical, spiritual, and religious values. They argue that, because these are ecosystem services, conservation of ecosystems services sometimes captures biodiversity and its values (see also 6, 7 ).…”
Section: Common Groundmentioning
confidence: 99%